A strategy for enhancing the teaching of English literacy to dyslexic foundation phase learners - Mbatha, Ncamisile Emelina (University of the Free State, 2018)
The literature indicates that there is a global outcry for learners who experience dyslexia in literacy (English) at an early stage of learning (foundation phase). As a result, these learners’ learning is impeded by this condition (dyslexia) and they are referred to special schools for persons with mental retardation. The aim of this study was to find a strategy to enhance the teaching literacy (English) to dyslexic foundation phase learners. Dyslexia is characterised by difficulties with accurate and/or fluent word recognition and by poor spelling and decoding abilities. The study adapted and adopted the principles of participatory action research as an approach and design to generate data. The critical emancipatory research principle was used as the theoretical framework that guided the study. The generated data was analysed using critical discourse analysis. This study has extensively explored the methods and strategies that responded adequately to learning needs of the dyslexic learners at the foundation phase. In pursuance of, and based on this aim, the study responded to the following objectives: to justify the need for development of the strategies to enhance the teaching of literacy (English) for learners with dyslexia in the foundation phase; to understand the conditions conducive for the implementation of suitable strategies, learning theories and styles in order to accommodate dyslexic learners; to determine the inherent risks and threats that might hinder optimal implementation of the strategies; and to provide the evidence of the optimal functionality and effectiveness of the envisaged strategies that could be used to teach dyslexic learners in the foundation phase. The study has alleviated the effect of dyslexia experienced by learners. The following were found to be helpful: equipping teachers with a multisensory curriculum designed to combine visual, auditory and kinaesthetic learning modalities, introduction of the teacher, therapy and parent programme, taking one day of therapy per week during the school day, adapting and enhancing methods of assessment and teaching to accommodate learner’s needs and diversity.
Dissertation (M.Ed. (School of Education Studies))--University of the Free State, 2018
Keywords: Teaching strategies; Learning approaches; Dyslexia and foundation phase